Homosynaptic plasticity induction causes heterosynaptic changes at the unstimulated neighbors in an induction pattern and location-specific manner - Argunsah, Ali Özgür; Israely, Inbal (Frontiers in Cellular Neuroscience, 2023)
Dendritic spines are highly dynamic structures whose structural and functional fluctuations depend on multiple factors. Changes in synaptic strength are not limited to synapses directly involved in specific activity patterns. Unstimulated neighboring synapses in and around the stimulated dendritic spine clusters can also undergo alterations in their strength. However, when plasticity is induced at single dendritic spines using glutamate uncaging, neighboring spines do not show any significant structural fluctuations. Here, using two-photon imaging and glutamate uncaging at single dendritic spines of the hippocampal pyramidal neurons, we show that the structural modifications at the unstimulated neighboring spines are a function of the temporal pattern of the plasticity-inducing uncaging stimulus and the relative location of the neighbors concerning the stimulated spine at the local dendritic segment.